Optimizing blockchain technology using a data sharing model - Nazeeh, Israa; Hussain Hadi, Teeb; Qahtan Mohammed, Zainab; Taha Ahmed, Shaymaa; Kanaan Kadhim, Qusay (Institute of Advanced Engineering and Science, 2023)
The improvement of different data-sharing technology has increasingly permeated many industries as technology continues to improve. As a result, for the value of the data to be realized, data sharing and security are essential. However, a fundamental data sharing mechanism is difficult to check for electronic data usage traces. Furthermore, data providers' unwillingness to provide their data is a challenge. Taking use of the dispersed ledger, smart contract, data trust, and traceability aspects of blockchain technology. This research presents a data-sharing model based on blockchain technology optimizing to overcome the challenges in terms of security and control, of conventional centralized data sharing and management, enabling safe access to the data as a result. Moreover, the research assesses the prototype's usefulness and security. Additionally, this paper suggests a method for using blockchain technology to optimize the efficiency of data sharing. This study showed that data sharing via the blockchain technology paradigm proposed in this work is feasible, secure, controllable, and efficient. This was demonstrated in a novel way employing blockchain technology.